2015
DOI: 10.1016/j.diagmicrobio.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pan-serotype reverse transcription loop-mediated isothermal amplification assay for the detection of dengue virus

Abstract: During dengue outbreaks, acute diagnosis at the patient's point of need followed by appropriate supportive therapy reduces morbidity and mortality. To facilitate needed diagnosis, we developed and optimized a reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay that detects all 4 serotypes of dengue virus (DENV). We used a quencher to reduce nonspecific amplification. The assay does not require expensive thermocyclers, utilizing a simple water bath to maintain the reaction at 63 °C. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Isothermal NAATs eliminate the need for power hungry thermal cyclers, significantly lowering the complexity of hardware required for these tests. RT-LAMP detection of dengue15161718, chikungunya19, and other RNA viruses has been demonstrated previously, and at least one recent report has demonstrated RT-LAMP detection of Zika virus13. In most cases, these reports detect amplification with non-specific indicators of total DNA synthesis, such as monitoring turbidity20, observing the color-change indicator hydroxynaphtol blue (HNB)17, performing a post-reaction analysis involving addition of an indicator dye ( e.g .…”
mentioning
confidence: 98%
“…Isothermal NAATs eliminate the need for power hungry thermal cyclers, significantly lowering the complexity of hardware required for these tests. RT-LAMP detection of dengue15161718, chikungunya19, and other RNA viruses has been demonstrated previously, and at least one recent report has demonstrated RT-LAMP detection of Zika virus13. In most cases, these reports detect amplification with non-specific indicators of total DNA synthesis, such as monitoring turbidity20, observing the color-change indicator hydroxynaphtol blue (HNB)17, performing a post-reaction analysis involving addition of an indicator dye ( e.g .…”
mentioning
confidence: 98%
“…The study showed that pan-serotype RT-LAMP could discriminate dengue with a sensitivity of 86%. This study also visualized the amplification of target gene on lateral flow assay [49]. In one study Lau et al employed hydroxynaphthol blue (HNB) dye for the colorimetric visualization of RT-LAMP-amplified product through the naked eye, thus, making the assay simpler as it does not require specific tool to interpret the LAMP product.…”
Section: Rt-lamp Platformmentioning
confidence: 99%
“…This process can be further accelerated by the addition of loop primers also targeted to the exposed single-stranded region of the loop (9). This technique has found widespread application primarily in the diagnosis and monitoring of infectious diseases such as malaria (10,11), West Nile virus (12,13) and dengue (14).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of quantitative LAMP for monitoring and control operations remains to be fully exploited. Until this point, most qLAMP assays have focused on ascertaining the concentrations of pathogens within specific infection contexts (e.g 14,21,29,30),. although studies have considered microorganismal eDNA(14), pathogenic viruses in water (31) and forensic applications (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation